Pulsar acceleration by asymmetric emission of sterile neutrinos (2002)
ABSTRACT: A convincing explanation for the observed pulsar large peculiar velocities is still missing. We argue that any viable particle physics solution would most likely involve the resonant production of a non-interacting neutrino vs of mass mvs ∼ 20–50 keV. We propose a model where anisotropic magnetic field configurations strongly bias the resonant spin flavour precession of tau antineutrinos into vs. For internal magnetic fields Bint >∼ 1015 G a ¯vt-vs transition magnetic moment of the order of 10−12 Bohr magnetons is required. The asymmetric emission of vs from the core can produce sizeable natal kicks and account for recoil velocities of several hundred kilometers per second.